Review of the structure and functioning of the Caribbean Community Secretariat : final report - Archer, Leonard...[et al.] (CARICOM Secretariat GeorgetownGY, 2002)
Looks at the role of the Institutions and Associate Institutions of the Community. Examines the process of decision-making and implementation. Proposes a framework and process for the continuous review and prioritisation of the various mandates and programmes of work of the Community, and particularly the CARICOM Secretariat. Reviews areas where there has already been decentralisation and recommends decentralisation of specific areas of the Secretariat.